Determinants Implementation of Policies Procurement and Distribution of Fertilizer Subsidized to farmers in the Southeast Minahasa, Indonesia - Kawuwung, Jeanne; Langkai, Jeane Elisabeth; Pangkey, Itje (Technium Social Sciences Journal, 2021)
The study is intended to analyze the implementation of policies fertilizer subsidy in the Eastern Tombatu subdistrict of Southeast Minahasa, Indonesia. The research uses qualitative research to understand the meaning behind the phenomenon related to implementing the policy procurement and distribution of fertilizer subsidized to farmers in the east Tombatu sub-district, Southeast Minahasa Regency. Data collection techniques, through the methods: a). Observation by making observations about the process of distributing subsidized fertilizers b). Interview with: 1) farmers using subsidized fertilizers, 2) distributor of fertilizer subsidized, 3). department of agriculture, which is in charge of the distribution of fertilizer subsidy. c). Documentation. 1). report the implementation of the policy implemented by the department of agriculture and distributors, 2) documents of fertilizer were distributed, 3) Policy documents. Research shows that the determinants of implementing policies fertilizer subsidy in the southeast Minahasa showed that: a). socialization of policies are outs implemented as of interest policy, b) The length of the bureaucratic structure tends to impact the scarcity of fertilizers when farmers need them. c) The scarcity of fertilizers is that farmers can not obtain subsidized fertilizer because there is no RDK (Definitive Needs Plan Group). In contrast, farmers do not know how to prepare RDK. d). low dispossess implementers to implement policies according to policy objectives. For it is suggested should be: a) do socialization about fertilizer policy subsidized effectively and efficiently to all the groups involved in implementing procedures, b) cut the bureaucratic structure that creates scarcity of fertilizers when farmers need it, c) farmers are taught how to make RDK, d) required a dispossess implementer who earnestly implements policies according to policy objectives, e) provide rewards and sanctions for implementers by their respective primary duties and functions.